2021
DOI: 10.4018/ijitlhe.20210101.oa2
|View full text |Cite
|
Sign up to set email alerts
|

Using Experiential Learning to Improve Student Attitude and Learning Quality in Software Engineering Education

Abstract: Experiential learning (EL) has great potential to transform students’ learning experience. Few studies, however, have focused on the use of EL in computer science education. The purpose of this study was to examine students' experiences with EL in computer science. Data were collected to examine the influence of EL on students' attitudes and quality of learning. The antecedent variables included student involvement, learning expectancy, instructor impact, course structure, and prior experience. PLS-SEM with PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…El-Glaly et al [24] suggested that incorporating EL into curricula inspired students to learn and value the importance of accessibility and take it into consideration while developing software. Thus, the impact of EL in positively enhancing students' learning and attitude towards software engineering education is significant [25]. Community engaged learning (CEL), a form of experiential learning has been an effective method to retain students in courses [26].…”
Section: B Experiential Learningmentioning
confidence: 99%
“…El-Glaly et al [24] suggested that incorporating EL into curricula inspired students to learn and value the importance of accessibility and take it into consideration while developing software. Thus, the impact of EL in positively enhancing students' learning and attitude towards software engineering education is significant [25]. Community engaged learning (CEL), a form of experiential learning has been an effective method to retain students in courses [26].…”
Section: B Experiential Learningmentioning
confidence: 99%
“…Thus, as declared by Kolb and Kolb ( 2005 ), EL can be depicted from a constructivist structure where information is made and reproduced in the student's individual information and not simply by passing on previous notions to the student (Kolb and Kolb, 2018 ). Through their endeavors, students build information, learn-by-doing as they participate in tackling issues, either alone or cooperatively, and critically ponder over bits of knowledge that arise (Watts et al, 2011 ; Che et al, 2021 ). Learners' involvement in solving problems in the learning system is the main contribution of EL, which is its innate characteristic.…”
Section: Introductionmentioning
confidence: 99%